KONTROVERSI PENC,GUNAAN AMALGAM ALLOY SEBAGAI BAHAN RESTORASI KARIES GIGI - Maria Martina Nahak (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Dental amalgam is the oldest restorative materials and the use of this material dominates others. Until now there has been no filling material in other types that can rival the advantages of dental analgam because of its strength to resist chewing, Ieast expensive, its longevity in the oral cavity, does not need to be changed frequently and rarely cause secondary caries. But recent controversies arise in its use because of the content of mercary in dental amalgan. WHO continue to support the use of dental amalgam on anyone, but dental workers must be manage amalgam waste strictly in accordance with the rules issued the WHO.